BANKING COMPETITION IN INTERNATIONAL BANKING SERVICES MARKET - Fattakhova Munisa Abdukhamitovna (Galaxy International Interdisciplinary Research Journal, 2023)
The article shows the peculiarities of competition in the international market of banking services. The specifics of the activities of subsidiary banks, branches of foreign banks, transnational banks in the banking system are described, the main areas of banking activity where banks can compete are listed